The Role of the Cooperative and Tourism Service (Diskopar) in Tourism Development in Dumai City - Rudi Hartasetiadi; Lilis Wahyuni; Ernita Puspa Dewi; Dewi Jannah; Mesi Yendara (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This study aims to analyze the role of the Department of Youth, Sports and Tourism (Diskopar) Dumai City in tourism development and to identify supporting and inhibiting factors affecting its implementation. The research uses a qualitative descriptive approach with data collected through interviews, observation, and documentation. Informants consisted of a tourism data and information officer at Diskopar Kota Dumai and a community tourism actor. The data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings show that Diskopar Kota Dumai plays an active role based on three role indicators: institutional position, social expectations, and implementation. The institution is involved not only in policy formulation but also in maintenance, monitoring, training workshops, event organization, and management of public tourism spaces. Supporting factors include regional tourism potential, digital promotion, regulatory documents, and regional budget support. Inhibiting factors include suboptimal maintenance of tourist sites, illegal levies in unmanaged areas, and uneven information access due to limited network coverage. Overall, the role of the Dumai City Diskopar is functioning but still requires strengthening in supervision, facility management, and equitable promotion.